The Effect of Current Ratio and Debt to Equity Ratio on Return On Assets in Real Estate Companies Listed on the IDX in 2020-2024 - Vinka Nashwa Sukmala; Dian Festiana Hadi Saputro; Imang Dapit Pamungkas; Lilis Setyowati (LP2M IAIN Palopo, 2026)
The Indonesian real estate sector experienced considerable fluctuations in financial performance during the period of economic disruption caused by the COVID-19 pandemic and the subsequent recovery phase. These conditions increased the importance of evaluating factors that influence corporate profitability, particularly Return on Assets (ROA), which reflects a company's effectiveness in utilizing its assets to generate earnings. Previous studies examining the relationship between liquidity, leverage, and profitability have produced inconsistent results, indicating the need for further investigation. Therefore, this study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) in real estate companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. This research employed a quantitative approach with a causal-descriptive design. Secondary data were obtained from audited annual reports published by the IDX. The sample was selected using purposive sampling, resulting in 135 firm-year observations. Data were analyzed using multiple linear regression supported by IBM SPSS version 23 after fulfilling the classical assumption tests. The results indicate that Current Ratio does not significantly affect Return on Assets, suggesting that liquidity is not a primary determinant of profitability in the real estate industry. In contrast, Debt to Equity Ratio has a significant negative effect on Return on Assets, indicating that higher leverage increases financial burdens and reduces profitability. Simultaneously, Current Ratio and Debt to Equity Ratio significantly explain variations in ROA. In conclusion, effective debt management plays a more important role than liquidity management in improving the profitability of real estate companies. Managers should therefore maintain an optimal capital structure to support sustainable financial performance.